Interaction of Nalbuphine Hydrochloride with Deoxyribonucleic Acid Measured by Fluorescence Quenching - Sultana, S.; Bin Sayeed, M. S.; Ahmed, M. U.; Islam, M. S.; Bahar, A.; Sultan, M. Z.; Hasnat, A. (Drug Research, 2013)
The interaction of nalbuphine hydrochloride with calf thymus deoxyribonucleic acid was investigated by absorption and fluorescence titration techniques. Hypochromic effect was observed in the absorption spectra of nalbuphine. The fluorescence quenching of nalbuphine by DNA was found to be static according to Stern-Volmer constant at different temperature (2.257×103  L/mol and 1.678×103  L/mol at 298 K and 308 K respectively; binding constants (K) between calf thymus DNA and nalbuphine were 2.081×103 and 8.26×101 at 298 K and 308 K respectively). The binding numbers (n) were 0.9955 and 0.6762 with the standard deviation of 0.225 at 2 different temperatures which indicates mol ratio of Nalbuphine and DNA remains unchanged at different temperatures (298 K and 308 K). The binding affinity of nalbuphine to DNA was calculated at different temperatures and the stoichiometry of binding was characterized to be about 1 nalbuphine molecule per nucleotide. Calibration for nalbuphine, based on quenching titration data, was linear in the concentration range 6.3×10−6 to 6.4×10−4  mol/L. And these binding forces also indicate the binding site of Nalbuphine to be at the minor groove of DNA.
Keywords: calf thymus DNA; affinity; stern volmer constant; fluorescence quenching; hypochromic effect; minor groove